Determining Radicalism And Violence In The Name Of Religion In Indonesia Through Local Wisdom Approach - Santy Karsa Tarigan; Muhamad Syauqillah (Pelopor Publikasi Akademika, 2023)
This article discusses strategies to counteract radicalism and violence in the name of religion through local wisdom approaches in Indonesia. This study aims to provide an analysis of how radicalism and violence in the name of religion occur in Indonesian society and to present a recommendation on a strategy for solving these problems through a local wisdom approach originating from the cultural heritage of the ancestors of the Indonesian people. The space for freedom at the beginning of the reform era, which went too far, has been used by certain parties to instill radical ideas that are contrary to Pancasila ideology. The entry of this radical understanding is often manifested in the form of violence in the name of religion. In general, there are five factors that encourage violence in the name of religion in Indonesia, namely: superiority, injustice, vulnerability, distrust and powerlessness. One strategy that can be used as a solution to overcome this problem is through a local wisdom approach. This article raises the culture that exists in the Fak-Fak – West Papua and Karo ethnic groups in North Sumatra as a role model as well as showing that local wisdom is very effective in controlling and controlling people's lives and is able to prevent the growth of radicalism and intolerance in society.